Separation of Monocytes from Whole Human Blood - John Graham (The Scientific World Journal)
Human peripheral blood monocytes are isolated by flotation from whole blood through a single low-density barrier prepared from OptiPrep™ at 4°C. The separation from lymphocytes depends on the more rapid rate of flotation of the monocytes because of their slightly lower density and larger size. The method works optimally only with fresh (within 2 h of drawing) EDTA-anticoagulated blood. Preliminary evidence suggests that this technique may be applicable to blood from rats.